Metabolic Dysfunction Associated Steatotic Liver Disease, Not Just Fatty Liver Disease: A Systemic Shift in Naming and Understanding - Tiwari, Pratap Sagar (Journal of Nobel Medical College, 2025)
The reclassification of fatty liver disease to Metabolic dysfunction-associated Steatotic Liver Disease (MASLD) marks a paradigm shift. Moving beyond stigmatizing, misleading terms, MASLD emphasizes metabolic dysfunction as the root cause. This systemic condition links to cardiovascular, renal, and diabetic risks, demanding comprehensive screening, research, and public health action worldwide.